WTO disciplines on agricultural support : seeking a fair basis for trade - Orden, David; Blandford, David; Josling, Tim (Timothy Edward), 1940- (Cambridge : Cambridge University Press, 2011)
'Farm support is contentious in international negotiations. This in-depth assessment of the legal compliance and economic evaluation issues raised by the WTO Agreement on Agriculture presents consistent support data and forward-looking projections for eight developed and developing countries (EU, US, Japan, Norway, Brazil, China, India, Philippines), using original estimates where official notifications are not available. Variations over time in notified support in some cases reflect real policy changes; others merely reflect shifts in how countries represent their measures. The stalled Doha negotiations presage significantly tighter constraints for developed countries that provide the highest support, but loopholes will persist. Developing countries face fewer constraints and their trade-distorting farm support can rise. Pressure points and key remaining issues if a Doha agreement is reached are evaluated. Vigilant monitoring for compliance of farm support with WTO commitments will be required to lessen its negative consequences whether or not the Doha Round is concluded'--
Machine generated contents note: Part I. Overview of Domestic Support Issues and WTO Rules: 1. Introduction David Orden, David Blandford and Tim Josling; 2. The WTO disciplines on domestic support Lars Brink; Part II. Developed Countries: Have High Levels of Support Come Down?: 3. European Union Tim Josling and Alan Swinbank; 4. United States David Blandford and David Orden; 5. Japan Yoshihisa Godo and Daisuke Takahashi; 6. Norway Ivar Gaasland, Roberto Garcia and Erling Vardal; Part III. Developing Countries: Will Low Levels of Support Rise?: 7. Brazil Andre Nassar; 8. India Munisamy Gopinath; 9. China Fuzhi Cheng; 10. Philippines Caesar B. Cororaton; Part IV. Looking Forward: Can Fair Markets Be Achieved?: 11. The difficult task of disciplining domestic support David Orden, David Blandford and Tim Josling; Appendix A. Domestic support provisions of the Agreement on Agriculture; Appendix B. Domestic support provisions of the Doha draft modalities.
Includes bibliographical references and index.
Keywords: World Trade Organization; Tariff on farm produce; Competition, Unfair